OPPORTUNITIES TO IMPROVE THE STANDARD OF LIVING OF THE POPULATION THROUGH THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Saydkhodjayeva Nigorakhon Ibaydullaevna (Ecominds Press, 2025)
This article is devoted to the issues of increasing the income of the population, improving their living standards, and ensuring the well-being of society through the development of small business and private entrepreneurship. It analyzes the concept of income in various forms of ownership, its sources of formation, and distribution mechanisms in the conditions of liberalization of the market economy.
Keywords: Small business, private entrepreneurship, market economy, employment, monostructure, polystructure, population income, humanitarian principle, legality, social protection, business environment.